(untitled) (Altre Modernità, 2018)
Texts and visuals in the online aesthetics of migration: Translation as (re)narration in the creative cultural industries Within the context of Computer-mediated communication discourse (Herring 1996; 2011, 2015), this study focuses on the investigation of Internet modalities and genres through which experiences of current migration are transferred from personal stories into online public narratives, also known as “transmedia storytelling” (Jenkins 2006; Jenkins, Ford, Green 2013). The art of telling migrant stories on the web produces acts of translation in terms of (re)statements of migrant lives. This mechanism owns a repository function, which is meant to spread narratives of migration by means of new media forms – including visual, textual and auditory genres – that collide with old media ones. Against a backdrop where contemporary migration crisis has gained a voice through the public narrativization of personal and collective experiences within aesthetic discourse in the creative cultural industries (Mathur 2011; Moslund 2015), emphasis is given on activist movements of artists and migrant storytellers from the perspective of narrative theory in translation and interpreting studies (Baker 2006; 2014; 2016a; 2016b). The corpus, composed of the three websites "Syrian Trojan Women", "Project#Refugeecameras", "Big Journeys-Untold Stories", and of the blog "Askavusa Collettivo–Port M", is scrutinized according to Luc Pauwels’s multimodal framework for the cultural analysis of websites (2012), in combination with Systemic Functional Language analysis and multimodality (Halliday, 1994; Kress and van Leeuwen 1996; 2001). Results show that online migrant repertoires are reconceptualized as acts of witnessing and deliberation (Chouliaraki 2016), and as counter narratives that give rise to forms of translation as participation and solidarity, protest and intervention.